Implementasi Literasi Membaca melalui Program Asesmen Nasional Berbasis Komputer di SDN 1 Karangklesem - Faiz Bariohinul Umam; Kharisma Nurul Abdika; Ibnu Abinnashih (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
This research aims to evaluate the implementation of the reading literacy program through the ANBK Program at SDN 1 Karangklesem. The research method used in this research is descriptive qualitative. The results of this research show that the reading literacy program through ANBK has had a positive impact on student preparation, increasing reading comprehension. There are several stages used by SSDN 1 Klarangklesem in implementing learning literacy through ANBK, namely: In the planning stage, the school principal forms an ANBK implementation committee consisting of the committee chairman, secretary, technician, and proctor. Next, students were given an ANBK simulation link to prepare them for answering numeracy questions, and study groups were formed before answering the questions to improve their understanding. During the implementation phase, students answer practice questions in the form of ANBK simulations and take part in dress rehearsal sessions. The teacher provides full assistance to help students understand the contents of the sentences and questions they read, as well as providing an understanding of the quick answer method in answering ANBK questions. The evaluation stage involves printing out the simulation results which the teacher evaluates. Questions that are difficult for students to answer become important evaluation points for teachers' and students' future development. Keywords: Assessment, Computers, Literacy.